2016
DOI: 10.1093/jxb/erv562
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase HDA9 negatively regulates salt and drought stress responsiveness in Arabidopsis

Abstract: Histone modification is an important epigenetic regulation in higher plants adapting to environment changes including salt and drought stresses. In this report, we show that the Arabidopsis RPD3-type histone deacetylase HDA9 is involved in modulating plant responses to salt and drought stresses in Arabidopsis. Loss-of-function mutants of the gene displayed phenotypes (such as seedling root growth and seed germination) insensitive to NaCl and polyethylene glycol (PEG) treatments. HDA9 mutation led to up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
142
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 39 publications
8
142
2
Order By: Relevance
“…Currently, however, there is no evidence demonstrating that recipient organisms use naturally produced HDIs from donor organisms to enhance stress tolerance. This and previous studies (Sako et al, 2016;Zheng et al, 2016) raise the possibility of the existence of HDI-mediated, symbiotic relationships that enhance abiotic stress tolerance. Further studies are necessary to elucidate the role of naturally produced metabolites with HDI properties in natural habitats.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Currently, however, there is no evidence demonstrating that recipient organisms use naturally produced HDIs from donor organisms to enhance stress tolerance. This and previous studies (Sako et al, 2016;Zheng et al, 2016) raise the possibility of the existence of HDI-mediated, symbiotic relationships that enhance abiotic stress tolerance. Further studies are necessary to elucidate the role of naturally produced metabolites with HDI properties in natural habitats.…”
Section: Discussionsupporting
confidence: 71%
“…However, it is possible that each HDAC may control the response to salt stress in a different manner among class I HDACs. hda9 and hda19 knockdown lines lead to the derepression of salt stress-responsive genes (Mehdi et al, 2016;Zheng et al, 2016). Considering the previous results from the functional analysis of HDA9 and the hda19 mutants in this study, both of which belong to class I HDACs, HDA9 and HDA19 negatively regulate salt stress-responsive genes.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…HDA9 regulates several biological processes, such as flowering time, seed dormancy, and stress responses (14,35,36,40,41). Although previous studies have shown that development and stress-response genes are up-regulated and this is accompanied by hyperacetylation in the hda9 mutant, there have been no reports about HDA9-interacting proteins required for its histone deacetylation function.…”
Section: Discussionmentioning
confidence: 99%